An Examination of the Indigenization Pathways of Rural Churches: A Case Study of the Anglican Church in Shandong - WANG, Siqi (Journal of Research for Christianity in China (JRCC), 2025)
Christianity experienced widespread dissemination in rural Shandong. Taking the Anglican church as an example, both the number of rural chapels and adherents continued to increase, with Chinese workers playing a pivotal role in this process. In the sphere of doctrinal transmission, they translated theological concepts into local idioms, thereby strengthening emotional identification among the populace. In religious practice, they mediated the tension between Christian culture and indigenous beliefs through the integration of miracle narratives and ritual performances. At the organizational level, the kinship-based dissemination of faith fostered the formation of local faith community. Institutionally, Chinese workers assumed leadership in church governance, advancing the principles of self-propagation, self-support, and self-governance. Consequently, the indigenization of rural churches in central Shandong entailed not merely an adaptation of doctrinal transmission but also a reshaping of language, ritual, social structures, and institutional forms. The indigenizing trajectory of rural Christianity was neither a simple transplantation of Western models nor a wholesale accommodation to local culture, but rather a synthesis of universality and locality achieved within the framework of faith identity.